EKOLEKSIKON KENELAYANAN DI PULAU MANDANGIN- MADURA - Naelur Rahmah; Mixghan Norman Antono (Bahtera Indonesia, 2023)
As a language study, this research is structured based on the basic assumption that Mandangin is a potential area for tourism development in Madura. This research offers a simple concept as an effort to make Mandangin a literacy-friendly tourist area in Madura by conducting an ecolexicon inventory based on the ecological conditions of the Mandangin people themselves. This research was conducted using a descriptive qualitative method. This method is used to apply ecological, sociolinguistic, and lexicological theories more comprehensively. The results of this study indicate that there are interesting fisheries ecolexicon treasures to be inventoried and then an analysis of lexical and grammatical meanings is carried out, namely marine biota ecolexicon treasures. The results of the inventory and meaning are then used as a reference in determining dimensional aspects including the biological dimension which refers to the use of biotic and abiotic terms, the sociological dimension which refers to social interaction, and the ideological dimension which is indicated by loyalty to tradition. Keywords: ecolexicon, fishermen, Mandangin Island